Façonner la ville : projets de société et stratégies de gouvernement à Grenoble (1910-2010) - Julien Caranton; Thomas Lerosier (Métropoles)
This article focuses, from the case of Grenoble, on urban governments in the 20th and 21st centuries. Two programmatic speeches shaped the city during this period: the first was formulated at the beginning of the 20th century and made Grenoble the nerve centre of a modern alpine region supported by hydroelectric industries. This project was terminated in the 1960s through restructuring of the industrial sector. A new discourse emerged in the early 1980s, presenting Grenoble as a city within the global network of innovative metropolises. In this article, we propose, on the one hand, to analyse how these discursive practices succeeded in establishing themselves as dominant social projects at the city level and, on the other hand, to see how they materialised within the urban fabric.